Ignition of Boron-Containing High-Energy Materials Based on an Oxidizer and Polymer Binder; Technical Physics; Vol. 66, iss. 6 - Korotkikh A. G. Aleksandr Gennadievich; Sorokin I. V. Ivan Viktorovich; Slusarskiy (Slyusarsky) K. V. Konstantin Vitalievich; Arkhipov V. A. Vladimir Afanasjevich (2021, 2021)
Title screen